Analisis Penggambaran Gender Dalam Laporan Tahunan Pada Perusahaan Sektor Perkebunan Di Indonesia Tahun 2016-2018 - Utari Wahyuli Purwasih; Herlina Helmy (Universitas Negeri Padang, 2020)
This study proposes to provide analysis and understanding of gender representation in the annual report of plantation companies in Indonesia. The objects of this research are PT Austindo Nusantara Jaya, PT Dharma Satya Nusantara and PT Sinar Mas Agro Resources and Technology. This research uses descriptive qualitative with secondary data types obtained from the Annual Report of PT Austindo Nusantara Jaya, PT Dharma Satya Nusantara and PT Sinar Mas Agro Resources and Technology. Data collection is done by collecting techniques with photographs of people in the company's annual report. The analytical method used is content analysis. The steps of this research are: 1) evaluating photos of people in the annual report, 2) grouping photos by employees or non-employees, only men, only women, or men and women together, 3) an overview of the number of photos by group, 4) interpret research results found in annual reports. The results showed that gender depictions in the annual report of PT Austindo Nusantara Jaya, PT Dharma Satya Nusantara and PT Sinar Mas Agro Resources and Technology does not support equality between men and women. Photos of employees in the annual report are approved by male sex compared to women. Through analysis of sex photographs discussed in the annual report, it was found that sex was supportive in terms of role, place, clothing, and body language. But in the analysis of relative positions, men and women choose to stand or sit together